Do Exchange Rates Work? : Another View - Mundell, Robert (IMF Working Papers; Working Paper ;, 1991)
This paper investigates the role of exchange rates in balance of payments theories. It explores the sixteen approaches to the balance of payments, the concept of an 'equilibrium' trade balance and sequential 'stages' of the current account. It examines fiscal and demographic influences on the U.S. deficit. The final section considers the breakdown of the international monetary system after World Wars I and II; an evaluation of alternative proposals to correct the defects of the system; and an examination of the extent to which deficits of reserve countries have their origins in systemic problems.